Narratives about Jews among Muslims in Norway: A qualitative interview study - Moe Bjørnbekk, Vibeke (Religious Minorities in the North History, Politics, and Culture, 2024)
What is the nature of Muslim-Jewish relations in Europe today? Based on qualitative interview data, this book explores narratives about Jews among Muslims in Norway. Drawing on culturally embedded narratives as well as personal experiences, interviewees reflect on the relationship between Jews and Muslims. The interreligious exchange between Islam and Judaism is as old as Islam. Today, the Arab-Israeli conflict has become an important frame of reference in the public discourse on Muslim-Jewish relations. The narratives presented in this book delineate shifting community boundaries and identifications that transcend dichotomised notions of "Muslims versus Jews." The analysis shows how Jewish history in Europe and the history of modern antisemitism serve as interpretative keys in the narratives, used for explaining the situation of the Muslim minority today. Furthermore, the book demonstrates how interviewees' perceptions of society's attitudes toward Muslim and Jewish experiences also strongly influence their perceptions of Muslim-Jewish relations.